Efektifitas Teknik Pijat Akupressure Terhadap Penununan Kadar Asam Urat pada Penderita Gout arthritis di Wilayah Puskesmas Bulango Ulu - Mokambu, Zulfikar (Jurnal Keperawatan Muhammadiyah, 2024)
Objective:Gout Arthritis is a metabolic disease caused by excess levels of urate compounds in the body, either due to excess production, insufficient elimination, or increased purine intake. One non-pharmacological therapy that has been proven to be able to overcome various health problems is acupressure. The aim of the research was to determine the effectiveness of the Acupressure Massage technique in reducing uric acid levels in Gouty Arthritis sufferers in the Bulango Ulu Health Center working area. Methods:The design of this research is quantitative research, using a quasi-experimental design with one group pretest-posttest, with a sample size of 13 respondents.. Results:The research results showThere was a decrease in uric acid levels after the Acupressure Massage Technique was carried out with the mean value before treatment being 9.392, while the mean value after treatment was 7.485. Where there is a difference in the mean value, namely 1.9077 with a p-value of 0.000, which means <0.05). Conclusion:The acupressure massage technique is very effective for reducing uric acid levels in sufferers of Gout Arthritis, of the elderly.